Comparison Between Sandwich Bone Augmentation and Allogenic Block Graft for Vertical Ridge Augmentation in the Posterior Mandible. Issue 1 (February 2015) - Leong, Daylene Jack-Min; Oh, Tae-Ju; Benavides, Erika; Al-Hezaimi, Khalid; Misch, Carl E.; Wang, Hom-Lay
Abstract : Introduction: The purpose of this randomized controlled clinical trial was to evaluate 2 different techniques for vertical ridge augmentation (VRA) of the posterior mandible. Materials and Methods: Sixteen subjects with 19 posterior mandibular edentulous sites requiring VRA were recruited for the study. Sites were randomly treated with either block allograft (BA; N = 9) or sandwich bone augmentation (SBA; N = 10). Clinical measurements were recorded at the time of surgery (baseline) and 6-month reentry with a custom-made acrylic surgical template. Results: The mean vertical bone gain (VBG) after mean 6.8 months was 44.5% (mean = 1.78 mm [0–5 mm]) in the BA group and 33.3% (mean = 1.0 mm [−1 to 3 mm]) in the SBA group. Significantly higher rates of incision line openings and wound dehiscences were found in the BA group (n = 7/9, 77.8%) as compared with the SBA group (n = 3/10, 30%) ( P = 0.037). After adjusting for graft exposure, BA group demonstrated significantly higher VBG than SBA (difference = 2.26 mm, P < 0.001). In addition, graft exposure resulted in significantly less VBG in both groups ( P < 0.001). Conclusions: A higher tendency of wound exposure during VRA was demonstrated when a BA was used compared with the SBA technique. However, if wound exposure could be prevented, higher vertical ridge gain could be achieved with a BA. Summary: The use of a BA in VRA resulted in a maximum of 2 mm more bone height gain compared with the SBA technique if the primary coverage can be achieved during the healing.